PENGARUH SINETRON 7 MANUSIA HARIMAU TERHADAP TINGKAT MENIRU ADEGAN KEKERASAN DIKALANGAN ANAK (Studi Kasus Di Daerah Bibis Luhur Rw 22 Kelurahan Nusukan, Kecamatan Banjarsari, Surakarta) - Dwi Nugroho, Antonius Christian (Transformasi, 2015)
This research, usedquantitative method research with the kind of research explanatory, aimedto explain the influence of watched7 Tigerman opera soap to imitative behaviorchildren.From the correlation product moment 0,923 is positive, and from the test t obtainedvalue tcalculate of 16,971 with the p-value of 0,000, prove that activity watched 7 Tigermanopera soap effect are significant and high evaluation of imitative behavior scene violence inthe Bibis Luhur Village RW 22, Nusukan urban village, Banjarsari sub-district, of Surakarta.Key Word: Opera Soap, Watching 7 Tigerman Opera Shop, Imitative Behavior